Effectivenees Of Mini Video Education On Anxiety In Section Caesarea Patients Undergoing Spinal Anesthesia - uliyanti; Aisyah Nur Azizah; Istiqomah Rosidah (Journal of Indonesian Anesthesiology Nursing, 2025)
Background: Sectio caesarea is a surgical procedure that involves making an incision in the abdominal wall and uterus to allow the fetus to be removed from the abdomen, namely from the mother's uterus. Patients who undergo sectio caesarea often feel anxious. Anxiety is a feeling of fear or worry that is not based on a real threat from the situation being experienced. This state of anxiety is generally characterized by fear that arises for no apparent reason. This anxiety can be overcome by providing non-pharmacological, namely providing education using mini videos. Objective: This study aims to measure the decrease in anxiety levels of caesarean section patients at PKU Muhammadiyah Gamping Hospital after watching a mini educational video on spinal anesthesia procedures. Methods: This type of research uses a quantitative research method with a Quasi Experimental research design with Nonequivalent Control Group Design. This design uses two groups, namely the experimental group and the control group. Sampling uses a purposive sampling technique with a total of 40 samples. Data analysis using the Mann-Whitney test Results: The Mann-Whitney test showed the results of the influence of mini video education on spinal anesthesia procedures for anxiety in caesarean section patients, as indicated by the results of the significance value P value <0.05 (P = 0.000 <0.05). Conclusion: There is the influence of visual media in the form of mini videos which present information more concisely so that it is easier to understand.